Adapting to climate change and multi-risk governance: toward sustainable adaptation and enhancing urban resilience—Indonesia - Abdillah Abdillah; Ida Widianingsih; Rd Ahmad Buchari; Heru Nurasa (Discover Applied Sciences)
Abstract Climate change has contributed to an increase in natural catastrophes over the past five years in Indonesia, causing various forms of damage in urban areas and posing a severe danger to multi-risk governance for municipal governments in Indonesia. This study explores how multi-risk governance strategies encourage sustainable adaptation to climate change and increase urban resilience in Bandung and Makassar City, Indonesia. This study method uses a qualitative-exploratory approach with a case study in two (2) climate-vulnerable cities in Indonesia. Data analysis uses qualitative-interactive analysis. The results of this study show that the impact of climate change in Bandung and Makassar City, Indonesia has caused an increase in the potential for erosion, reduced wetlands along the coast, an increase in the rate of seawater intrusion, a decrease in food production, damage to infrastructure, a reduction in clean water sources, an increase in disease. respiratory, floods, droughts, and other hydrological disasters. This has resulted in many climate approaches and actions being taken to respond to the impact of climate change in Indonesia (Bandung and Makassar City), the results of which are still not optimal to date. This study suggests a sustainable adaptation approach to climate action in Bandung and Makassar City which prioritizes social justice and environmental integrity so that it has a real impact on community vulnerability and environmental damage due to the impacts of climate change. The contribution of this study provides sufficient insight into the institutional approaches and adaptive sustainability measures needed to promote resilience in Indonesia. At the same time, this study will be a useful reference in future research on multi-risk governance and sustainable adaptation strategy for climate action and enhancing urban governance.